2016
DOI: 10.1177/1534735416673907
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q0 Enhances Ultraviolet B–Induced Apoptosis in Human Estrogen Receptor–Positive Breast (MCF-7) Cancer Cells

Abstract: Coenzyme Q0 (CoQ0; 2,3-dimethoxy-5-methyl-1,4-benzoquinone), a major active constituent of Antrodia camphorata, has been shown to inhibit human triple-negative breast cancer (MDA-MB-231) cells through induction of apoptosis and cell-cycle arrest. Ecological studies have suggested a possible association between ultraviolet B (UVB) radiation and reduction in the risk of breast cancer. However, the underlying mechanism of the combination of CoQ0 and UVB in human estrogen receptor–positive breast cancer (MCF-7) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…It possesses strong antioxidant activity and prevents the mitochondrial permeability transition pore [18] from being opened calcium-dependently. CoQ 0 has demonstrated activity against the proliferation of numerous cancer cell lines (e.g., HepG2, A549, and SW480) [19, 20]. Although it exhibits cytotoxic anticancer activities, it was also demonstrated to stimulate insulin secretion in pancreatic islets [21].…”
Section: Introductionmentioning
confidence: 99%
“…It possesses strong antioxidant activity and prevents the mitochondrial permeability transition pore [18] from being opened calcium-dependently. CoQ 0 has demonstrated activity against the proliferation of numerous cancer cell lines (e.g., HepG2, A549, and SW480) [19, 20]. Although it exhibits cytotoxic anticancer activities, it was also demonstrated to stimulate insulin secretion in pancreatic islets [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that 300 mg per day is a common dosage of commercial products of coenzyme Q10 ( 81 ). Published research used coenzyme Q10 at concentrations from 5–60 µM ( 64 , 82 , 83 ). The present study used CoQ10 at concentrations of 1, 5 and 10 µM that are achievable in the plasma of CoQ10 supplement-consuming individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Since cancer cells perform high-level metabolic activity and suffer from more oxidative stress ( 63 ), antioxidants could potentially promote the growth and progression of cancers by mopping up free radicals from cancer cells. In fact, our previous research has demonstrated that antioxidant vitamin C exerted a stimulatory effect at physiological concentration on the growth and metastasis of human malignant melanoma ( 64 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the family of coenzyme Q consisting of a benzoquinone structure conjugated to an isoprenoid chain from C0 to C10. CoQ 0 has the potential activity to suppress inflammation, cancer, and metabolic diseases (Wang et al, 2017). The inhibitory effect of CoQ 0 on S. aureus development has also been reported in previous studies (Fan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%